HUBUNGAN FEAR OF MISSING OUT (FoMO) DENGAN CYBERBULLYING YANG DIMODERASI DENGAN INTENSITAS PENGGUNAAN MEDIA SOSIAL PADA REMAJA PENGGUNA PLATFORM TIKTOK DI DAERAH ISTIMEWA YOGYAKARTA - Aulia Putri; Ratna Yunita Setiyani Subardjo Subardjo (Prodi Psikologi- Fakultas Psikologi & Humaniora - Universitas Teknologi Sumbawa, 2026)
This study aims to examine the relationship between Fear of Missing Out (FoMO) and cyberbullying behavior moderated by social media usage intensity among TikTok-using adolescents in the Special Region of Yogyakarta. This research employed a quantitative approach with simple linear regression and moderation analysis involving 151 respondents. Data were collected through questionnaires and analyzed using Jamovi. The results indicate that FoMO and social media usage intensity have a very strong and significant positive relationship with cyberbullying (r = 0.935; p < 0.05), contributing 87.4%. However, social media usage intensity does not act as a moderator (p > 0.05). These findings suggest that FoMO and social media usage intensity function as direct predictors of cyberbullying. The study implies the importance of managing adolescents’ social media use and psychological factors to reduce cyberbullying behavior.